Eksistensi Homestay di Desa Wisata Wringinputih Kabupaten Magelang Pada Masa Covid-19 The Existence of Homestay in the Wringinputih Tourism Village Magelang Regency during Covid-19 Period - Fachrurrozi, Muchammad Syarif; Lasally, Adesty (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2023)
This study aims to determine the efforts of Homestay management in increasing the number of room occupancy in the Wringinputih tourist village, Magelang district after the Covid-19 pandemic. This study uses a descriptive approach using a qualitative method. Retrieval of data sources using purposive sampling technique by collecting observation data, interviews, and documentation. The results showed that the existence of homestays in the tourist village of Wringinputih, Magelang district during the Covid-19 pandemic included: 1) Planning, by increasing marketing and promotion by providing online Food Beverage Service, 2) Organizing, the process of organizing the existence of homestays during a pandemic is carried out by increasing Human Resources (HR), namely by reducing employees, scheduling work, and paying employees on a daily basis. 3) Movement, the Wringinputih homestay continues to increase cooperation with the government and travel and tourism agents by providing attractive promos such as the Pay Now Stay Letter. 4) Supervision, the application of the Health Protocol is carried out with a general procedure known as 3M, namely washing hands, wearing masks and maintaining distance